2020
DOI: 10.1542/peds.2020-009951
|View full text |Cite
|
Sign up to set email alerts
|

Racial and/or Ethnic and Socioeconomic Disparities of SARS-CoV-2 Infection Among Children

Abstract: OBJECTIVES: To evaluate racial and/or ethnic and socioeconomic differences in rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection among children. METHODS: We performed a cross-sectional study of children tested for SARS-CoV-2 at an exclusively pediatric drive-through and walk-up SARS-CoV-2 testing site from March 21, 2020, to April 28, 2020. We performed bivariable and multivariable logistic regression to measure the association of patient race and/or ethnicity and estimated median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
179
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 13 publications
9
179
2
7
Order By: Relevance
“…As infections with SARS-CoV-2 and its associated illness, COVID-19, have surged across the world, multiple studies have identified higher rates of infection, hospitalization, and mortality among minority populations. [1][2][3][4][5][6][7][8][9][10][11][12] Disparities in infection rates exist even among healthcare workers 13 and children, 14,15 with disparities in mortality rates greatest among young individuals 16 and growing as the pandemic spreads. 17 To date, the relative contributions of pathophysiologic and socioeconomic factors contributing to these disparities remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As infections with SARS-CoV-2 and its associated illness, COVID-19, have surged across the world, multiple studies have identified higher rates of infection, hospitalization, and mortality among minority populations. [1][2][3][4][5][6][7][8][9][10][11][12] Disparities in infection rates exist even among healthcare workers 13 and children, 14,15 with disparities in mortality rates greatest among young individuals 16 and growing as the pandemic spreads. 17 To date, the relative contributions of pathophysiologic and socioeconomic factors contributing to these disparities remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomically disadvantaged children had a higher likelihood of SARS-CoV-2 infection. 23 Examples of the consequences of the focus on COVID are given in papers from the United Kingdom, which report on possible collateral damage, including decreased vaccination, decreased attendance at hospitals and delayed diagnosis of diseases, as well as the negative impact of isolation on mental well-being. 24,25 Therefore, there is the potential for the following areas of research.…”
Section: Collateral Damage Of the Lockdown And Social Distancingmentioning
confidence: 99%
“…The consequences are similar to the upper-income countries, but lack of resources and other comorbidities may lead to different outcomes. [45][46][47] In particular, the impact of the decrease in preventive measures such as vaccination, maybe worse than the impact of the infection from the SARS-CoV-2 infection. 48 Research into the global impact on children is urgently required as the social determinants of healthcare is a global issue.…”
mentioning
confidence: 99%
“…For example, in a survey of over 13 000 adolescent athletes throughout the country during the COVID-19 restrictions in May 2020, we found that 40% reported moderate to severe depression symptoms and 37% reported moderate to severe anxiety. 3 The burden of COVID-19 has disproportionately affected low income and minority children, 4 and unfortunately this appears to be true in youth sports as well. In the same nationwide survey, we found that adolescent athletes from areas with the highest levels of poverty reported the lowest physical activity levels and the highest levels of depression and anxiety.…”
Section: Impacts Of Covid-19 Restrictions On Young Athletesmentioning
confidence: 99%